Case Report: A small cell lung cancer transformed from an EGFR-mutated Adenocarcinoma demonstrated a long-term remission to anti PD-1 antibody - Kawanaka, Yusuke; Yonesaka, Kimio; Tanizaki, Junko; Maenishi, Osamu; Sakai, Kazuko; Kakimi, Kazuhiro; Nishio, Kazuto; Hayashi, Hidetoshi (Frontiers in Oncology, 2025)
Transformation to small cell lung cancer (SCLC) is a resistance mechanism in epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) after EGFR-tyrosine kinase inhibitor (EGFR-TKI) treatment. The efficacy of immune checkpoint inhibitor (ICI) in transformed SCLC remains to be elucidated. The present case report highlights a patient whose tumor underwent transformation to SCLC after developing resistance to an EGFR-TKI treatment. The patient subsequently achieved long-term remission lasting more than 5 years through treatment with an anti-PD-1 antibody nivolumab. Generally, the efficacy of ICI is inferior in EGFR-mutated NSCLC compared to those with EGFR wild-type NSCLC. However, some cases that have transformed to SCLC may be sensitive to ICI treatment. Further investigation is necessary to determine the efficacy of ICI in cases that have undergone transformation to SCLC.